SURVEY OF GRAFT KIDNEY FUNCTION CHARACTERISTICS AND SOME RELATED FACTORS IN KIDNEY TRANSPLANT RECIPIENTS AT MILITARY HOSPITAL 175 - Dang Thanh Phuong,; Nguyen Cong Binh,; Duong Xuan Minh,; Nguyen Viet Cuong,; Tran Quoc Viet, (Tạp chí Y học Quân sự, 2026)
Objective: To evaluate early graft kidney function and influencing factors in living-donor kidney transplant recipients. Subjects and Methods: A prospective descriptive study was conducted on 52 living-donor kidney transplant recipients at Military Hospital 175 from July, 2023 to May, 2025. Assessment of graft function post‑transplant by serum creatinine concentration and GFR during the first three months after kidney transplantation. Results: Most kidney recipients were male (65.4%), with a mean age of 42.3 ± 12.2 years. The mean age of kidney donors was 35.7 ± 7.2 years, and the mean HLA mismatch was 2.8 ± 1.2. Estimated glomerular filtration rate (eGFR) at one month and three months post-transplant was 67.2 ± 16.3 ml/min/1.73m² and 63.8 ± 15.9 ml/min/1.73m², respectively, with no statistically significant difference. Recipient age over 50 years and an age difference greater than 10 years between donor and recipient were associated with lower estimated glomerular filtration rate (eGFR) at one month post-transplant. Among recipients with Tacrolimus concentrations > 5 ng/ml, rapid Tacrolimus metabolizers had a lower estimated glomerular filtration rate (eGFR) at 3 months post-transplant compared with slow or intermediate metabolizers (55.8 ml/min/1.73 m² versus 67.1 ml/min/1.73 m²; p = 0.015). The change in estimated glomerular filtration rate (eGFR) was also less favorable in the rapid metabolizer group (-8.0 ml/min/1.73m² versus -1.0 ml/min/1.73m²; p = 0.032). Conclusion: At three months after kidney transplantation, graft kidney function remained stable, with no patient mortality and a low rate of acute rejection. The rapid Tacrolimus metabolism associated with an early decline in estimated glomerular filtration rate (eGFR) may inform the development of monitoring strategies and individualized immunosuppressive therapy in clinical practice.